A Dual-Band SiGe HBT Frequency-Tunable and Phase-Shifting Differential Amplifier Employing Varactor-Loaded, Stacked LC Resonators. (21st October 2012) - Sakamoto, Kazuyoshi; Itoh, Yasushi
Abstract : A dual-band SiGe HBT frequency-tunable and phase-shifting differential amplifier has been developed for the future active phased array antennas with a multiband, multibeam, and multitarget tracking operation. The amplifier uses varactor-loaded, stacked LC resonators in the design of the output circuit in order to provide frequency-tunable and phase-shifting capabilities for dual frequencies. By utilizing the varactor-loaded LC resonator, which has a variable resonant frequency and a large insertion phase variation, frequency-tunable and phase-shifting performances become available. Moreover, by using the stacked configuration, the frequency and insertion phase can be varied independently for dual frequencies. A dual-band SiGe HBT differential amplifier has achieved a lower-frequency tuning range of 0.56 to 0.7 GHz for a higher fixed frequency of 0.97 GHz as well as a higher-frequency tuning range of 0.92 to 1.01 GHz for a lower fixed frequency of 0.63 GHz. A lower-frequency phase variation of 99° and a higher-frequency phase variation of 90.3° have been accomplished at 0.63 and 0.97 GHz, respectively. This is the first report on the dual-band differential amplifier with frequency-tunable and phase-shifting capabilities.